Synthesis and Corrosion Test of Magnesium Zinc-5% Hydroxyapatite (MgZn-5% wt.Hap) Biocomposites as a Bone Biodegradable Implant Material: Henni Sitompul, Kiagus Dahlan, Deni Noviana, Marzuki Silalahi, Sulistioso Giat Sukaryo, Yohanes Edi Gunanto - Henni Sitompul Henni Sitompul; Kiagus Dahlan Kiagus Dahlan; Deni Noviana Deni Noviana; Marzuki Silalahi Marzuki Silalahi; Sulistioso G. Sukaryo Sulistioso G. Sukaryo; Yohanes E. Gunanto Yohanes E. Gunanto (Jurnal Fisika dan Aplikasinya, 2019)
In recent years, development of magnesium (Mg) as biodegradable implant very rapidly in orthopedic applications. This is due to its young’s modulus close to young modulus of natural bone. However, Mg implants demonstrate higher biological activity which could cause high degradation rate in human bio-environment. Consequently, needed to develop Mg-based alloys with superior corrosion performance. In the present study, it has been attempted to develop biocomposite of Magnesium Zinc-5% Hydroxyapatite (MgZn-5%HAp) as biodegradable bone implant. The biocomposites were prepared by adding 5wt.% powders to MgZn powder and then were sintered at temperature 350 oC in vacuum furnace for holding an hour. The characterization of MgZn-5wt%HAp biocomposite was examined by Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM/EDS) and X-ray diffraction (XRD) while corrosion tested by potensiostat. The SEM / EDS and XRD results indicated that some of the Zn atoms have dissolved in Mg to form a MgZn solid solution. The SEM results also showed that the MgZn-5%HAp biocomposite has a microstructure with a matrix Mg and HAp at the grain boundary. The presence of HAp in the sample resulted in a smaller crystallite size and corrosion rate compared to the one with MgZn alloy.